Transformações do carbono e do nitrogênio no solo e produção de aveia com o uso de dejetos de suínos em plantio direto - Marques, Marcelo Gonçalves (2005)
The use of pig manure, especially of the deep-bedding manure, is not so often in the winter cover crops, preceding the summer commercial plantation. The aim of this study was to evaluate the carbon and nitrogen dynamics in soil and the black oat production with the use of pig slurry and deep-bedding manure. Emphasis has been given to the losses of N for ammonia volatilization, to the variation in the amounts of mineral N, to the decomposition of the organic materials and the oat N accumulation. Three experiments were conducted in field conditions in a typic Hapludalf soil, at the experimental area of the Soil Science Department, Federal University of Santa Maria, Santa Maria, RS, from May to October of 2003. In the first experiment, the ammonia volatilization was evaluated after the application of the pig slurry and deep-bedding manure on the crop residues of corn, in the following treatments: T1 - crop residues of corn (RCM) + 44,2 m3 ha-1 of pig slurry; T2 - RCM + 17,9 Mg ha-1 deep-bedding; T3 - RCM without incorporation; T4 - RCM + 44,2 m3 ha-1 pig slurry with incorporation and T5 - RCM with incorporation. The N losses by ammonia volatilization were higher in deep-bedding manure than in the pig slurry, proportionally. No loss of the N for ammonia volatilization was observed with the incorporation of the pig slurry in the soil. The highest ammonia emissions for the atmosphere (65%) occurred during the first day after the application of the pig slurry and the deep-bedding manure in the field. In the second experiment the N dynamics was evaluated in the soil during the black oat cultivation, through the temporary variation of the amounts of mineral N (NNH4+ and N-NO2- + N-NO3-). Also, the dry matter production and N accumulation in oat in the following treatments: T1 crop residues of corn (RCM) + 44,2 m3 ha-1 of pig slurry of ; T2 - RCM + 17,9 Mg ha-1 of deep-bedding manure; T3 - RCM + 9,7 Mg ha-1 of deep-bedding manure; T4 - RCM + 50 kg ha-1 of N-urea and T5 - RCM. For equivalent amounts of mineral N applied to the soil with the deep-bedding manure and the pig slurry, the amount of mineral N in the soil was higher in the pig slurry, evidencing a lower rate of mineralization of organic N of the deep-bedding manure. The ammoniacal N of the pig slurry was quickly nitrified in the soil and N-NO3- produced moved in the soil profile. This shows the evidences of lossing N by lixiviation. The deep-bedding manure presented low potential of supply of N to the oat, compared to the pig slurry. Only 22.5% of the ammoniacal N applied with the pig slurry was recovered in the oat. In the physiologic maturation of the oat 52.6% of ammoniacal N applied with the pig slurry was found in the soil-plant system. In the third experiment was evaluated the effect of the addition of pig manure on the decomposition of the crop residues of corn (RCM), without incorporation to the soil. The emission of C-CO2 was quantified continually for 62 days in the following treatments: T1 - Soil + RCM + 44,3 m3 ha-1 of pig slurry; T2 - Soil + RCM + 17,9 Mg ha-1 deep-bedding manure; T3 - Soil + RCM; T4 - Soil + 44,3 m3 ha-1 of pig slurry; T5 - Soil + 17,9 Mg ha-1 deep-bedding manure and T6 - Soil. The decomposition was higher in the pig slurry than in the deep bedding, revealing the highest degree of recalcitrant of the carbon compost of the deep-bedding manure. The decomposition of the crop residues of corn, with high C/N ratio, was improved with the application to the pig slurry.